2018
DOI: 10.1007/s00405-018-5150-x
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography accelerates staging in patients with Merkel cell carcinoma

Abstract: PurposeNo imaging algorithms for diagnostic imaging in patients suffering from Merkel cell carcinoma (MCC) have been established so far and thus staging work-up is challenging. Long presentation-to-treatment intervals determine further treatment course and, consequently, have an impact on clinical outcome in patients with MCC.MethodsIn this retrospective study, diagnostic imaging of 37 MCC patients was analyzed. CT, ultrasound, and PET/PET–CT imaging for primary staging work-up with time frames from patients´ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…23 In a study evaluating delays in treatment time for MCC, CT imaging was identified as expediting staging and recommended as a preliminary imaging modality. 24 Another study advocated that 18F-FDG PET-CT had a high impact on management, leading to a change in disease staging in 33%. 25 In our study, imaging overall had moderate sensitivity and specificity of identifying occult disease, 56% and 62%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 In a study evaluating delays in treatment time for MCC, CT imaging was identified as expediting staging and recommended as a preliminary imaging modality. 24 Another study advocated that 18F-FDG PET-CT had a high impact on management, leading to a change in disease staging in 33%. 25 In our study, imaging overall had moderate sensitivity and specificity of identifying occult disease, 56% and 62%.…”
Section: Discussionmentioning
confidence: 99%
“…In a report of 112 patients, Colgan et al reported sensitivity and specificity of CT, magnetic resonance imaging, and PET to be 47% and 97%, 0% and 86%, 83% and 95%, respectively 23 . In a study evaluating delays in treatment time for MCC, CT imaging was identified as expediting staging and recommended as a preliminary imaging modality 24 . Another study advocated that 18F‐FDG PET‐CT had a high impact on management, leading to a change in disease staging in 33% 25 .…”
Section: Discussionmentioning
confidence: 99%